Sabrina Sue loves the moon - Burris, Priscilla (Ready-to-read. Star reader!, 2023)
Determined to blast off into outer space despite her barnyard friends' warnings, plucky chicken Sabrina Sue may just prove them wrong with her out-of-this-world adventure.